Metal foil with carrier

By clamping the peeling functional layer of metal nitrogen oxide in the metal foil with a carrier, the problems of rising peeling strength and increasing foreign matter particles at high temperatures are solved, and stable peelability and high-quality circuit formation are achieved.

CN114845863BActive Publication Date: 2025-03-04MITSUI MINING & SMELTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180007276.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-04
Filing Date
2021-01-21
Publication Date
2025-03-04
Estimated Expiration
2041-01-21

AI Technical Summary

Technical Problem

During the manufacturing process of multi-layer printed circuit boards, when the metal foil with a carrier is heated at high temperature, the peel strength is prone to excessively increase, resulting in loss of peelability, and at the same time, there is a problem of increasing foreign matter particles, which affects the circuit formation of subsequent processes.

Method used

By sandwiching the release functional layer containing metal nitrogen oxides between the carrier-containing metal foil and the metal layer, the number of foreign matter particles on the surface of the metal layer is suppressed, circuit formation is improved, and a stable peel strength is maintained at a high temperature of 240°C or above.

Benefits of technology

Maintaining a stable peel strength at high temperatures is achieved, increasing foreign matter particles is suppressed, and the quality and consistency of circuit formation are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114845863B_ABST
    Figure CN114845863B_ABST
Patent Text Reader

Abstract

Provided is a metal foil with a carrier that can suppress the number of foreign particles on the surface of a metal layer to improve circuit formation and can maintain stable releasability even after being heated for a long time at a high temperature of 240°C or higher (e.g., 260°C). The metal foil with a carrier comprises a carrier, a releasable functional layer provided on the carrier and containing a metal nitride oxide, and a metal layer provided on the releasable functional layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal foil with a carrier. Background Art

[0002] In recent years, in order to increase the mounting density of printed circuit boards and achieve miniaturization, the multilayering of printed circuit boards has become widely practiced. In many portable electronic devices, such multilayer printed circuit boards are used for the purpose of weight reduction and miniaturization. In addition, the thickness of the interlayer insulating layer of the multilayer printed circuit board is required to be further reduced and the circuit board is further lightweight.

[0003] As a technology that meets this requirement, a method for manufacturing a multilayer printed circuit board using a coreless build-up method is adopted. The coreless build-up method refers to a method in which a so-called core substrate is not used, but an insulating layer and a wiring layer are alternately stacked (built up) to form a multilayer. In the coreless build-up method, in order to easily peel off the support body and the multilayer printed circuit board, a scheme of using a metal foil with a carrier is proposed. For example, Patent Document 1 (Japanese Patent Publication No. 2005-101137) discloses a method for manufacturing a package substrate for mounting semiconductor elements, which includes: pasting an insulating resin layer on the carrier surface of a copper foil with a carrier to form a support body, forming a first wiring conductor on the extremely thin copper layer side of the copper foil with a carrier through processes such as photoresist processing, pattern electrolytic copper plating, and resist removal, stacking insulating materials and performing hot pressing processing to form a build-up wiring layer, peeling off the support substrate with a carrier, and removing the extremely thin copper layer.

[0004] In the manufacturing process of such a multilayer printed circuit board, a hot press process is performed each time insulating materials are stacked, so the metal foil with a carrier is heated at a high temperature for a long time. In addition, the heating temperature of the hot press process depends on the curing temperature of the insulating material to be stacked, so the temperature varies depending on the type of insulating material. It is known that the higher the heating temperature of the hot press process, the more the peel strength will increase excessively, resulting in a loss of peelability.

[0005] As a metal foil with a carrier that can cope with the increase in peel strength associated with heating, a method of providing a peeling layer comprising a metal oxide and carbon is proposed. For example, Patent Document 2 (International Publication No. 2019 / 131000) discloses a copper foil with a carrier, which sequentially comprises a carrier, an intermediate layer composed of a specified metal, a peeling layer comprising a metal oxide layer and a carbon layer, an etching stopper layer and an ultra-thin copper layer provided as desired, and by providing the above-mentioned specified peeling layer, even after long-term heating at a high temperature of more than 350°C, stable peelability can be maintained. In addition, the document also records: In order to further reduce the thickness of the ultra-thin copper layer in the copper foil with a carrier, an intermediate layer, a carbon layer, an ultra-thin copper layer, etc. are formed by sputtering.

[0006] In addition, it is also known that the metal foil with a carrier stabilizes the peel strength by having a metal oxide layer. For example, Patent Document 3 (Japanese Patent Publication No. 2017-88970) discloses: for a copper foil with a carrier having a carrier, an intermediate layer containing nickel, and an ultra-thin copper layer in sequence, after forming the intermediate layer and before forming the ultra-thin copper layer, an oxide layer (NiO2) is formed on the surface of the nickel by drying the intermediate layer at 30 to 100°C for 1 to 300 seconds. According to Patent Document 3, the deviation of the peel strength after the ultra-thin copper layer side of the copper foil with a carrier is pasted on an insulating substrate and crimped at 220°C × 2 hours can be well suppressed.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-101137

[0010] Patent Document 2: International Publication No. 2019 / 131000

[0011] Patent Document 3: Japanese Patent Application Publication No. 2017-88970 Summary of the invention

[0012] As described above, in the manufacturing process of a multilayer printed circuit board, the substrate is heated each time an interlayer insulating material is stacked, and therefore, the metal foil with a carrier is expected to have heat resistance at a high temperature of, for example, 240° C. or higher. In this regard, the metal foil with a carrier having an intermediate layer containing Ni and NiO2 disclosed in Patent Document 3 has a stable peel strength at a low level at a hot pressing temperature of about 220° C., as described above, but cannot cope with hot pressing at a higher temperature of 240° C. or higher.

[0013] On the other hand, as disclosed in Patent Document 2, by using a metal foil with a carrier having a peeling layer including a metal oxide layer and a carbon layer, it is possible to maintain stable peelability even after heating at high temperature for a long time. However, it is found that when a carbon layer is formed as a peeling layer and a metal layer is formed thereon, the number of foreign particles on the surface of the metal layer increases compared to a case where no carbon layer is formed (for example, a case where a metal layer is directly formed on a glass carrier). There is a concern that the foreign particles may affect the formation of circuits in subsequent processes. Therefore, a metal foil with a carrier that can maintain heat resistance and suppress the number of foreign particles is sought.

[0014] The inventors of the present invention have obtained the following insight: by sandwiching a peeling functional layer containing a specified metal nitride between a carrier and a metal layer of a metal foil with a carrier, it is possible to provide a metal foil with a carrier that can suppress the number of foreign particles on the surface of the metal layer to improve circuit forming properties and can maintain stable peeling strength even after being heated for a long time at a high temperature of more than 240°C (for example, 260°C).

[0015] Therefore, an object of the present invention is to provide a metal foil with a carrier that can suppress the number of foreign particles on the metal layer surface to improve circuit formability and maintain stable releasability even after long-term heating at a high temperature of 240°C or higher (eg, 260°C).

[0016] According to one embodiment of the present invention, there is provided a metal foil with a carrier, comprising:

[0017] Carrier;

[0018] a release functional layer disposed on the aforementioned carrier and comprising a metal oxynitride; and

[0019] The metal layer is disposed on the aforementioned release functional layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view showing one embodiment of the metal foil with a carrier of the present invention.

[0021] Figure 2 This is a schematic cross-sectional view showing another embodiment of the metal foil with a carrier of the present invention.

[0022] Figure 3 This is a schematic cross-sectional view showing the layer structure of the metal foil with a carrier of Example 11 (comparison) in the examples.

[0023] Figure 4 This is a graph showing changes in the number of foreign particles on the surface of the metal layer due to the presence or absence of a carbon layer. DETAILED DESCRIPTION

[0024] Metal foil with carrier

[0025] An example of the metal foil with a carrier of the present invention is schematically shown in Figure 1 and Figure 2 .like Figure 1 and Figure 2As shown, the metal foil with a carrier 10 of the present invention comprises a carrier 12, a peeling function layer 14 and a metal layer 16 in this order. The peeling function layer 14 is a layer provided on the carrier 12 and containing metal nitride oxide. The metal layer 16 is a layer provided on the peeling function layer 14. In this way, by sandwiching the peeling function layer 14 containing metal nitride oxide between the carrier 12 and the metal layer 16 of the metal foil with a carrier 10, it is possible to provide a metal foil with a carrier that can suppress the number of foreign particles on the surface of the metal layer 16 to improve circuit forming properties, and can maintain stable peeling strength even after being heated for a long time at a high temperature of 240°C or more (for example, 260°C).

[0026] As described above, the metal foil with a carrier having an intermediate layer including Ni and NiO2 disclosed in Patent Document 3 has a stable low level of peel strength at a hot pressing temperature of about 220°C, but cannot cope with hot pressing processing at high temperatures such as 240°C or above. On the other hand, as disclosed in Patent Document 2, by using a metal foil with a carrier having a peeling layer including a metal oxide layer and a carbon layer, stable peeling properties can be maintained even after heating at high temperatures for a long time. However, according to the opinions of the present inventors, there is a concern that the peeling layer including a carbon layer may affect the circuit formation in the subsequent process. That is, the results of the investigation conducted by the present inventors found that: when a carbon layer is formed as a peeling layer and a metal layer is formed thereon, the number of foreign particles on the surface of the metal layer will increase compared to the case where no carbon layer is formed. As an example, Figure 3 The number of foreign matter particles (having a particle size of 5 μm or more) present per square centimeter on the surface of the first metal layer 122 in a metal foil 110 with a carrier having, in sequence, a carrier 112 made of glass, a bonding layer 114 made of Ti, a peeling auxiliary layer 116 made of Cu, a carbon layer 118 as a peeling layer, a second metal layer 120 made of Ti, and a first metal layer 122 made of Cu, and a metal foil 110′ with a carrier having a first metal layer 122 made of Cu formed on a carrier 112 made of glass is shown in FIG. Figure 4 It should be noted that Figure 4 In FIG. 1 , the bar graph on the left shows the number of foreign particles in the metal foil 110 ′ with a carrier without the carbon layer 118, and the bar graph on the right shows the number of foreign particles in the metal foil 110 with a carrier with the carbon layer 118. Figure 4 It is clear that the metal foil 110 with a carrier having the carbon layer 118 has three times more foreign particles on the surface of the first metal layer 122 than the metal foil 110' with a carrier without the carbon layer 118. Therefore, there is a concern that the foreign particles may affect circuit formation in the subsequent process.

[0027] In contrast, the metal foil 10 with a carrier of the present invention has a peeling function layer 14 containing metal nitride instead of a carbon layer. It is believed that the metal foil 10 with a carrier can effectively suppress the increase in the number of foreign particles on the surface of the metal layer 16, and as a result, the circuit formation in the subsequent process can be carried out well. Moreover, the metal foil 10 with a carrier having a peeling function layer 14 containing metal nitride can maintain a stable peeling strength even after being heated for a long time at a high temperature of more than 240°C (for example, 260°C). That is, it can be considered that since the peeling function layer 14 contains metal nitride, the excessive increase in peeling strength associated with heating can be suppressed. As a specific indicator of peeling strength, it is 260°C, 30kgf / cm 2 The pressure after pressurization for 2 hours is preferably 3 gf / cm or more and less than 50 gf / cm, more preferably 3 gf / cm or more and less than 30 gf / cm.

[0028] The material of the carrier 12 can be any of glass, ceramics, silicon, resin and metal. The carrier 12 is preferably composed of glass, silicon or ceramics. The form of the carrier 12 can be any of a sheet, a film and a plate. In addition, the carrier 12 can be stacked with these sheets, films and plates. For example, the carrier 12 can function as a rigid support such as a glass plate, a ceramic plate, a silicon wafer, a metal plate, etc., or it can be a non-rigid form such as a metal foil, a resin film, etc. Preferred examples of metals constituting the carrier 12 include copper, titanium, nickel, stainless steel, aluminum, etc. Preferred examples of ceramics include aluminum oxide, zirconium oxide, silicon nitride, aluminum nitride, and various other fine ceramics. Preferred examples of resins include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyamide, polyimide, nylon, liquid crystal polymer, polyether ether ketone (PEEK (registered trademark)), polyamide-imide, polyether sulfone, polyphenylene sulfide, polytetrafluoroethylene (PTFE), ethylene tetrafluoroethylene (ETFE), etc. From the viewpoint of preventing the warping of the coreless support body associated with heating when mounting electronic components, a material having a coefficient of thermal expansion (CTE) of less than 25ppm / K (typically 1.0ppm / K or more and 23ppm / K or less) is more preferred. Examples of such materials include various resins such as those mentioned above (especially low thermal expansion resins such as polyimide and liquid crystal polymer), glass, silicon, and ceramics, etc. In addition, from the viewpoint of ensuring handling and flatness during chip mounting, the Vickers hardness of the carrier 12 is preferably 100HV or more, and more preferably 150HV or more and 2500HV or less. As a material satisfying these characteristics, the carrier 12 is preferably composed of glass, silicon or ceramics, more preferably composed of glass or ceramics, and particularly preferably composed of glass. As the carrier 12 composed of glass, for example, a glass plate can be cited. When glass is used as the carrier 12, it has the advantages of being able to make the surface of the metal layer 16 extremely smooth due to its light weight, low thermal expansion coefficient, high insulation, rigidity and flat surface. In addition, when the carrier 12 is glass, there are the following advantages: it has surface flatness (coplanarity) that is advantageous for forming fine circuits; it has chemical resistance in desmearing in the wiring manufacturing process and in various plating processes; when the carrier 12 is peeled off from the metal foil 10 with the carrier, a chemical separation method can be used; etc. As preferred examples of glass constituting the carrier 12, quartz glass, borosilicate glass, alkali-free glass, soda-lime glass, aluminosilicate glass and combinations thereof can be cited, and alkali-free glass, soda-lime glass and combinations thereof are more preferred, and alkali-free glass is particularly preferred. Alkali-free glass is glass containing substantially no alkali metal, including silicon dioxide, aluminum oxide, boron oxide, and alkaline earth metal oxides such as calcium oxide and barium oxide as main components and further containing boric acid.The alkali-free glass has a thermal expansion coefficient as low as 3 ppm / K or more and 5 ppm / K or less in a wide temperature range of 0°C to 350°C and is stable, and therefore has the advantage of being able to minimize the warping of the glass in the process associated with heating. The thickness of the carrier 12 is preferably 100 μm or more and 2000 μm or less, more preferably 300 μm or more and 1800 μm or less, and further preferably 400 μm or more and 1100 μm or less. If the thickness is within this range, it is possible to ensure appropriate strength that does not hinder processing, and to achieve thinning of wiring and reduction of warping generated when electronic components are mounted.

[0029] The surface of the carrier 12 adjacent to the peeling functional layer 14 preferably has an arithmetic mean roughness Ra of 0.1 nm or more and 70 nm or less measured using a laser microscope in accordance with JIS B0601-2001, more preferably 0.5 nm or more and 60 nm or less, further preferably 1.0 nm or more and 50 nm or less, particularly preferably 1.5 nm or more and 40 nm or less, and most preferably 2.0 nm or more and 30 nm or less. As such, the smaller the arithmetic mean roughness of the carrier 12 surface, the more an ideal low arithmetic mean roughness Ra can be achieved at the surface of the metal layer 16 on the opposite side of the peeling functional layer 14 (the outer surface of the metal layer 16), and thus, at the wiring formed using the metal layer 16, it is suitable for forming a wiring pattern with a highly miniaturized line / space (L / S) of 13 μm or less / 13 μm or less (e.g., 12 μm / 12 μm to 2 μm / 2 μm).

[0030] The peeling functional layer 14 is a layer sandwiched between the carrier 12 and the metal layer 16 and contributes to the stable peeling of the carrier 12. From the viewpoint of maintaining stable peeling strength even after long-term heating at a high temperature of 240°C or higher (e.g., 260°C), the peeling functional layer 14 is a layer containing metal nitride oxides, preferably containing at least one metal nitride oxide selected from the group consisting of TaON, NiON, TiON, NiWON, and MoON, more preferably containing at least one selected from the group consisting of TaON, NiON, TiON, and MoON, further preferably containing at least one selected from the group consisting of TaON, NiON, and TiON, and particularly preferably containing at least one selected from the group consisting of TaON and TiON. In addition, regarding the peeling functional layer 14, from the viewpoint of ensuring the adhesion between the carrier 12 and the metal layer 16, the surface on the carrier 12 side preferably contains at least one selected from the group consisting of Cu, Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN, more preferably contains at least one selected from the group consisting of Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN, further preferably contains at least one selected from the group consisting of Ti, Ni, Al, Mo, W, TiN and TaN, and particularly preferably contains at least one selected from the group consisting of Ti, Al and TaN. The content of the above metal or metal nitride on the surface of the carrier 12 side of the peeling functional layer 14 is 30 atomic % or more, preferably 40 atomic % or more, more preferably 50 atomic % or more, further preferably 60 atomic % or more, particularly preferably 70 atomic % or more, and most preferably 80 atomic % or more. The upper limit of the content of the above metal or metal nitride is not particularly limited, and may be 100 atomic %, typically 98 atomic % or less. The metal or metal nitride has good compatibility with the material of the carrier 12, and can ensure adhesion. By controlling the content to the above range, stable adhesion can be ensured even after heating at high temperature for a long time, so it is preferred. These contents are set to values ​​measured by analysis using X-ray photoelectron spectroscopy (XPS).

[0031] On the other hand, from the same viewpoint as above, the surface of the stripping functional layer 14 on the opposite side to the carrier 12 (i.e., the metal layer 16 side) preferably contains at least one metal nitride selected from the group consisting of TaON, NiON, TiON, NiWON and MoON, more preferably contains at least one selected from the group consisting of TaON, NiON, TiON and MoON, further preferably contains at least one selected from the group consisting of TaON, NiON and TiON, and particularly preferably contains at least one selected from the group consisting of TaON and TiON. In the present invention, for the metal nitride, O and N can be contained in any proportion relative to the metal component constituting the metal nitride (for example, Ta when the metal nitride is TaON). ​​In other words, the metal nitride in the present invention can be represented by the general formula MO x N y (wherein, M is a metal component such as Ta, Ni, Ti, NiW, Mo, etc., and x and y are each independently a real number greater than 0) is expressed by the basic composition. However, for the surface of the stripping functional layer 14 on the opposite side of the carrier 12, the atomic ratio of O constituting the metal nitride relative to the metal component is preferably 4% or more (more preferably 5% or more and 120% or less), and the atomic ratio of N constituting the metal nitride relative to the metal component is preferably 20% or more (more preferably 25% or more and 45% or less). For the surface of the stripping functional layer 14 on the opposite side of the carrier 12, the content of the metal component constituting the metal nitride is preferably 20% or more and 80% or less, more preferably 25% or more and 75% or less, further preferably 30% or more and 70% or less, and particularly preferably 35% or more and 68% or less.

[0032] From the viewpoint of being able to effectively suppress the number of foreign particles on the surface of the metal layer 16, the stripping functional layer 14 preferably does not include a carbon layer (i.e., a layer whose main component is carbon). Among them, the stripping functional layer 14 may contain inevitable impurities caused by raw material components, film forming processes, etc. In addition, although not particularly limited, when the stripping functional layer 14 is exposed to the atmosphere after film formation, the presence of carbon dioxide and the like that are inevitably mixed therein may be allowed. From the above viewpoint, the carbon content of the stripping functional layer 14 measured by XPS may be below the detection lower limit, but typically below 3 atomic %, more typically below 1 atomic %. It should be noted that the measured value of the outermost surface (depth 0 nm) based on XPS tends to increase the carbon content due to dirt, etc. when exposed to the atmosphere, and therefore, the above-mentioned carbon content in the stripping functional layer 14 is set to the value at a position 2 nm deep (SiO2 sputtering rate conversion) from the surface (i.e., the surface of the stripping functional layer 14 on the opposite side of the carrier 12). The release functional layer 14 may be produced by any method, but is particularly preferably a layer formed by a magnetron sputtering method using a target from the viewpoint of being able to improve the uniformity of film thickness distribution.

[0033] The thickness of the peeling functional layer 14 is preferably 5 nm to 500 nm, more preferably 10 nm to 400 nm, further preferably 20 nm to 200 nm, and particularly preferably 30 nm to 100 nm. The thickness is set to a value measured by analyzing a layer cross section using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope.

[0034] The release function layer 14 may be Figure 1 As shown in the figure, it is a one-layer structure, and it can also be Figure 2 As shown, it is a structure of two or more layers.

[0035] According to a preferred embodiment of the present invention, the peeling functional layer 14 is as follows Figure 2 As shown, it includes an adhesion layer 14a and a release layer 14b.

[0036] The adhesion layer 14a has a function of relatively improving the interface adhesion between the carrier 12 and the peeling functional layer 14 so that stable peeling occurs at the interface between the peeling functional layer 14 and the metal layer 16. The adhesion layer 14a is preferably a layer comprising at least one selected from the group consisting of Cu, Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN, more preferably a layer comprising at least one selected from the group consisting of Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN, further preferably a layer comprising at least one selected from the group consisting of Ti, Ni, Al, Mo, W, TiN and TaN, and particularly preferably a layer comprising at least one selected from the group consisting of Ti, Al and TaN. The content of the above-mentioned metal or metal nitride in the adhesion layer 14a measured by X-ray photoelectron spectroscopy (XPS) is preferably 30 atomic % or more, more preferably 40 atomic % or more, further preferably 50 atomic % or more, further preferably 60 atomic % or more, particularly preferably 70 atomic % or more, and most preferably 80 atomic % or more. The upper limit of the content of the above-mentioned metal or metal nitride in the adhesion layer 14a is not particularly limited, and can be 100 atomic %, and is realistically 98 atomic % or less. In addition, although not particularly limited, when the adhesion layer 14a is exposed to the atmosphere after film formation, the presence of oxygen mixed therein can be allowed. The oxygen content of the adhesion layer 14a measured by X-ray photoelectron spectroscopy (XPS) is typically 0.1 atomic % or more and 10 atomic % or less, more typically 0.3 atomic % or more and 7 atomic % or less, and further typically 0.5 atomic % or more and 5 atomic % or less. The adhesion layer 14a can be manufactured by any method, and from the viewpoint of being able to improve the uniformity of the film thickness distribution, it is particularly preferred to be a layer formed by a magnetron sputtering method using a target. The thickness T1 of the adhesion layer 14a is preferably 5 nm or more and 400 nm or less, more preferably 10 nm or more and 300 nm or less, further preferably 50 nm or more and 200 nm or less, and particularly preferably 50 nm or more and 100 nm or less. The thickness is a value measured by analyzing the layer cross section using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope.

[0037] The peeling layer 14b is preferably a layer provided on the adhesion layer 14a and comprising at least one metal nitride selected from the group consisting of TaON, NiON, TiON, NiWON and MoON, more preferably a layer comprising at least one selected from the group consisting of TaON, NiON, TiON and MoON, further preferably a layer comprising at least one selected from the group consisting of TaON, NiON and TiON, and particularly preferably a layer comprising at least one selected from the group consisting of TaON and TiON. The atomic ratio of O constituting the metal nitride to the metal component measured by X-ray photoelectron spectroscopy (XPS) of the peeling layer 14b is preferably 4% or more (more preferably 5% or more and 120% or less), and the atomic ratio of N constituting the metal nitride to the metal component is preferably 20% or more (more preferably 25% or more and 45% or less). In addition, the content of the metal component constituting the metal nitride oxide measured by X-ray photoelectron spectroscopy (XPS) of the peeling layer 14b is preferably 20 atomic % or more and 80 atomic % or less, more preferably 25 atomic % or more and 75 atomic % or less, further preferably 30 atomic % or more and 70 atomic % or less, and particularly preferably 35 atomic % or more and 68 atomic % or less. The peeling layer 14b may contain unavoidable impurities caused by raw material components, film forming steps, etc. The peeling layer 14b can be manufactured by any method. From the viewpoint of being able to easily control the film thickness by adjusting the film forming time, it is preferably a layer formed by a reactive sputtering method using a metal target or a metal nitride target and sputtering in an atmosphere containing oxygen and / or nitrogen. In addition, the peeling layer 14b can also be formed by treating the surface of the adhesion layer 14a in oxygen plasma and / or nitrogen plasma using a commercially available plasma ashing device. Furthermore, when the adhesion layer 14a includes a metal nitride (ie, TiN and / or TaN), the separation layer 14b can also be produced by exposing the adhesion layer 14a formed in a vacuum to an oxidizing atmosphere (eg, air).

[0038] The thickness T2 of the stripping layer 14b is preferably 1 nm or more and 150 nm or less, more preferably 3 nm or more and 130 nm or less, further preferably 10 nm or more and 120 nm or less, and particularly preferably 50 nm or more and 100 nm or less. The stripping layer 14b can be formed thicker than the conventional stripping layer (carbon layer) composed of carbon. In this regard, by increasing the thickness T2 of the stripping layer 14b (for example, T2 is 50 nm or more), the stripping layer 14b can also function as an etching stopper. That is, the above-mentioned metal nitride oxide constituting the stripping layer 14b has the property of not being easily dissolved in the flash etching solution (for example, Cu flash etching solution), and as a result, it can exhibit excellent chemical resistance to the flash etching solution. Therefore, the stripping layer 14b becomes a layer that is not easily etched by the flash etching solution compared to the metal layer 16 described later, and therefore, it can also function as an etching stopper.

[0039] The thickness T2 of the peeling layer 14b can be determined by performing a depth-direction elemental analysis of the metal foil 10 with a carrier using X-ray photoelectron spectroscopy (XPS) according to the conditions described in the embodiments described later. It should be noted that in the depth-direction elemental analysis using XPS, even when the same etching conditions are used, the etching rate varies depending on the type of material, so it is difficult to obtain the value of the thickness T2 of the peeling layer 14b itself. Therefore, regarding the above-mentioned thickness T2, the etching rate calculated from the SiO2 film with a known film thickness is used, and the SiO2 conversion thickness calculated from the time required for etching is used. As a result, the thickness can be determined without doubt, and thus it can be evaluated quantitatively.

[0040] Regarding the metal foil 10 with a carrier, the ratio of the thickness T1 of the adhesion layer 14a to the thickness T2 of the release layer 14b, that is, T1 / T2, is preferably 0.03 or more and 400 or less, more preferably 0.07 or more and 300 or less, further preferably 0.1 or more and 200 or less, and particularly preferably 0.38 or more and 100 or less. By setting T1 / T2 within the above range, it is possible to suppress the reduction of the release function of the release function layer 14 when heat treatment is performed in a wide temperature range including, for example, a high temperature range of 100°C or more and 260°C or less. The mechanism by which the thickness ratio of the adhesion layer 14a to the release layer 14b affects the release property is still uncertain, but it is considered that this is because: by changing the above thickness ratio, the diffusion behavior of the elements constituting each layer of the metal foil 10 with a carrier during heating changes.

[0041] The metal layer 16 is a layer composed of metal. The metal layer 16 is preferably composed of at least one metal or alloy selected from the group consisting of transition elements of Groups 4, 5, 6, 9, 10 and 11 and Al, more preferably composed of at least one metal or alloy selected from the group consisting of transition elements of Groups 4 and 11, Pt, Al, Nb, Co, Ni and Mo, further preferably composed of at least one metal or alloy selected from the group consisting of transition elements of Group 11, Pt, Ti, Al and Mo, further preferably composed of at least one metal or alloy selected from the group consisting of Cu, Au, Pt, Ti and Mo, particularly preferably composed of at least one metal or alloy selected from the group consisting of Cu, Au and Pt, and most preferably composed of Cu. The above-mentioned metal constituting the metal layer 16 may be a pure metal or an alloy. The content of the above-mentioned metal measured by X-ray photoelectron spectroscopy (XPS) of the metal layer 16 is preferably 60 atomic % or more, more preferably 70 atomic % or more, further preferably 80 atomic % or more, and particularly preferably 90 atomic % or more. In addition, the upper limit of the content of the above-mentioned metal in the metal layer 16 is not particularly limited, and can be 100 atomic %, typically 98 atomic % or less. The metal constituting the metal layer 16 may contain unavoidable impurities caused by raw material components, film forming processes, etc. The metal layer 16 is preferably a layer formed by a gas phase method such as sputtering. The metal layer 16 is preferably an unroughened metal layer, but as long as it does not hinder the formation of the wiring pattern when manufacturing the printed circuit board, it can be a metal layer that has undergone secondary roughening by pre-roughening, soft etching treatment, cleaning treatment, and oxidation-reduction treatment. The thickness T3 of the metal layer 16 preferably has a thickness of more than 10nm and less than 1000nm, more preferably more than 20nm and less than 900nm, further preferably more than 30nm and less than 700nm, particularly preferably more than 50nm and less than 600nm, more particularly preferably more than 70nm and less than 500nm, and most preferably more than 100nm and less than 400nm. The thickness is set to a value measured by analyzing the cross section of the layer using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope. From the perspective of the in-plane uniformity of the film thickness, the productivity when the sheet and roll are formed, the manufacture of the metal layer 16 of the thickness in the above range is preferably carried out by sputtering.

[0042] The surface of the metal layer 16 on the opposite side to the release functional layer 14 (the outer surface of the metal layer 16) preferably has an arithmetic mean roughness Ra of 1.0 nm or more and 100 nm or less measured in accordance with JIS B 0601-2001, more preferably 2.0 nm or more and 40 nm or less, further preferably 3.0 nm or more and 35 nm or less, particularly preferably 4.0 nm or more and 30 nm or less, and most preferably 5.0 nm or more and 15 nm or less. As such, the smaller the arithmetic mean roughness, the more suitable it is for forming a highly miniaturized wiring pattern to the extent of line / space (L / S) of 13 μm or less / 13 μm or less (e.g., 12 μm / 12 μm to 2 μm / 2 μm) in a printed wiring board manufactured using the metal foil 10 with a carrier.

[0043] The metal layer 16 can be composed of one layer or more than two layers. In addition, as long as the metal foil 10 with a carrier has a carrier 12, a stripping functional layer 14 and a metal layer 16 in sequence, other layers can be included as long as the original function of the metal foil 10 with a carrier is not damaged. As an example of such other layers, an etching stopper layer as shown in patent document 2 (International Publication No. 2019 / 131000), a barrier layer (for example, a layer composed of Ti, Ta, Ni, W, Cr, Pd or a combination thereof) for suppressing the metal (for example, Au or Pt) constituting the metal layer 16 and the metal (for example, Cu) constituting the wiring layer that can be formed on the metal layer 16 (that is, the surface of the metal foil 10 with a carrier on the opposite side of the carrier 12) can be listed. In addition, the metal foil 10 with a carrier can be made into a structure that has the above-mentioned various layers in sequence on both sides of the carrier 12 in a manner that is symmetrical from top to bottom.

[0044] The overall thickness of the metal foil 10 with a carrier is not particularly limited, and is preferably 500 μm or more and 3000 μm or less, more preferably 700 μm or more and 2500 μm or less, further preferably 900 μm or more and 2000 μm or less, and particularly preferably 1000 μm or more and 1700 μm or less. The shape and size of the metal foil 10 with a carrier are not particularly limited, and are preferably rectangular or square in shape with one side being 10 cm or more, more preferably 20 cm or more, and further preferably 25 cm or more. The upper limit of the size when the metal foil 10 with a carrier is set to a rectangle or a square is not particularly limited, and as a reference for the upper limit, one side thereof can be set to 1000 cm. In addition, the metal foil 10 with a carrier is in a form that can be handled separately by itself before and after the wiring is formed.

[0045] Method for producing metal foil with carrier

[0046] The metal foil 10 with a carrier of the present invention can be manufactured by preparing the above-mentioned carrier 12, and forming a stripping functional layer 14 (for example, a bonding layer 14a and a stripping layer 14b) and a metal layer 16 on the carrier 12. From the viewpoint of easily coping with the fine pitch brought about by ultra-thinning, the formation of each layer of the stripping functional layer 14 and the metal layer 16 is preferably carried out by a physical vapor deposition (PVD) method. As examples of physical vapor deposition (PVD) methods, sputtering, vacuum evaporation and ion plating can be listed. From the viewpoint of being able to control the film thickness in a wide range of 0.05nm to 5000nm, and being able to ensure the uniformity of the film thickness in a wide width or area, sputtering is most preferably used. Film formation based on the physical vapor deposition (PVD) method can be carried out using a known vapor phase film forming device and in accordance with known conditions, without particular limitation. For example, when adopting sputtering method, the sputtering mode can be known various methods such as magnetron sputtering, bipolar sputtering method, and opposing target sputtering method, but from the viewpoint of fast film forming speed and high productivity, magnetron sputtering is preferably used. Sputtering can be carried out with any power supply in DC (direct current) and RF (high frequency). In addition, the target shape can also use a widely known plate-type target, but from the viewpoint of target use efficiency, it is desirable to use a cylindrical target. Below, the film formation based on physical vapor deposition (PVD) method (preferably sputtering method) for each layer of the close-fitting layer 14a, the peeling layer 14b and the metal layer 16 is described.

[0047] Regarding the film formation of the adhesion layer 14a based on the physical vapor deposition (PVD) method (preferably the sputtering method), from the viewpoint of being able to improve the uniformity of the film thickness distribution, it is preferred to use a target composed of at least one metal and / or metal nitride selected from the group consisting of Cu, Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN, and to perform magnetron sputtering in a non-oxidizing atmosphere. The purity of the target is preferably above 99.9wt%. As the gas used for sputtering, it is preferred to use an inert gas such as argon. The flow rate of argon gas, etc. can be appropriately determined according to the sputtering chamber size and the film forming conditions, and is not particularly limited. In addition, from the viewpoint of no abnormal discharge, poor plasma irradiation and other operational problems, and continuous film formation, it is preferred to perform the film formation with a pressure in the range of 0.1Pa or more and 20Pa or less. This pressure range can be set by adjusting the film forming power, the flow rate of argon gas, etc. according to the device structure, capacity, exhaust capacity of the vacuum pump, the rated capacity of the film forming power supply, etc. In addition, considering the uniformity of film thickness and productivity, the sputtering power per unit area of ​​the target was 0.05 W / cm 2 Above and 10.0W / cm 2 It may be appropriately set within the following range.

[0048] Regarding the film formation of the stripping layer 14b based on the physical vapor deposition (PVD) method (preferably the sputtering method), from the viewpoint of being able to easily control the film thickness, it is preferred to use a target composed of at least one metal and / or metal nitride selected from the group consisting of Ta, Ni, Ti, NiW, Mo, TiN and TaN, and to perform the sputtering by reactive sputtering in an atmosphere containing oxygen and / or nitrogen. The purity of the target is preferably above 99.9%. As the gas used in sputtering, it is preferred to include a gas for generating metal nitride (such as oxygen, nitric oxide gas and nitrogen dioxide gas) on the basis of an inert gas (such as argon gas). The flow rates of these gases can be appropriately determined according to the sputtering chamber size and the film forming conditions, and are not particularly limited. In addition, from the viewpoint of continuously performing film formation without malfunctioning such as abnormal discharge, it is preferred to perform the film formation with a pressure in the range of 0.1 Pa or more and 1.0 Pa or less during the film formation. This pressure range can be set by adjusting the film forming power and the flow rate of the above gases according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of film thickness and productivity, the sputtering power is 0.05W / cm per unit area of ​​the target. 2 Above and 15.0W / cm 2 It may be appropriately set within the following range.

[0049] Regarding the film formation of the metal layer 16 based on the physical vapor deposition (PVD) method (preferably the sputtering method), it is preferred to use a target composed of at least one metal selected from the group consisting of transition elements of Groups 4, 5, 6, 9, 10 and 11, and Al, and to carry out the process under an inert atmosphere such as argon. The target is preferably composed of a pure metal or an alloy, and may contain unavoidable impurities. The purity of the target is preferably 99.9% or more, more preferably 99.99%, and further preferably 99.999% or more. In order to avoid the temperature rise during the gas phase film formation of the metal layer 16, a cooling mechanism for the mounting table may be provided during sputtering. In addition, from the perspective of stable film formation without abnormal discharge, poor plasma irradiation, and other operational malfunctions, it is preferred that the pressure during film formation be in the range of 0.1 Pa or more and 20 Pa or less. The pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of film thickness and productivity, the sputtering power per unit area of ​​the target was 0.05 W / cm 2 Above and 10.0W / cm 2 It may be appropriately set within the following range.

[0050] Example

[0051] The present invention will be described in more detail by the following examples.

[0052] Example 1

[0053] like Figure 2 As shown, the release functional layer 14 (adhesion layer 14a and release layer 14b) and the metal layer 16 are sequentially formed on a glass sheet as a carrier 12 to produce the metal foil with a carrier 10. The specific steps are as follows.

[0054] (1) Preparation of vector

[0055] A glass sheet (material: soda-lime glass, arithmetic mean roughness Ra: 0.6 nm) having a thickness of 1.1 mm was prepared.

[0056] (2) Formation of the adhesion layer

[0057] A TaN layer having a thickness of 100 nm was formed as the adhesion layer 14a by sputtering on the carrier 12. The sputtering was performed using the following apparatus and under the following conditions.

[0058] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0059] -Target: 8-inch (203.2 mm) diameter TaN target (purity 99.95% or more)

[0060] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0061] -Gas: Argon (flow rate: 100 sccm)

[0062] -Sputtering pressure: 0.35Pa

[0063] -Sputtering power: 1000W (3.1W / cm 2 )

[0064] -Film forming temperature: 40℃

[0065] (3) Formation of the peeling layer

[0066] The sample on which the adhesion layer 14a was formed was taken out of the vacuum and exposed to the air for 5 minutes, thereby performing a surface oxidation treatment (natural oxidation) on the adhesion layer 14a. By this surface oxidation treatment, a TaON layer was formed as the release layer 14b.

[0067] (4) Formation of metal layer

[0068] A Cu layer having a thickness of 300 nm was formed as the metal layer 16 on the release layer 14 b by sputtering using the following apparatus and conditions, thereby obtaining the metal foil 10 with a carrier.

[0069] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0070] - Target: 8-inch (203.2 mm) diameter Cu target (99.98% purity)

[0071] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0072] -Gas: Argon (flow rate: 100 sccm)

[0073] -Sputtering pressure: 0.35Pa

[0074] -Sputtering power: 1000W (3.1W / cm 2 )

[0075] -Film forming temperature: 40℃

[0076] Example 2

[0077] The metal foil with a carrier 10 was produced in the same manner as in Example 1 except that a TiON layer was formed by reactive sputtering as follows instead of performing surface oxidation treatment of the adhesion layer 14a by atmospheric exposure as the release layer 14b.

[0078] (Formation of TiON Layer)

[0079] A TiON layer having a target thickness of about 100 nm was formed on the surface of the adhesion layer 14 a by reactive sputtering using the following apparatus and conditions.

[0080] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0081] -Target: 8-inch (203.2 mm) diameter TiN target (purity 99.95% or more)

[0082] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0083] -Gas: Argon (flow rate: 90 sccm) and Oxygen (flow rate: 10 sccm)

[0084] -Sputtering pressure: 0.35Pa

[0085] -Sputtering power: 100W (0.3W / cm 2 )

[0086] -Film forming temperature: 40℃

[0087] Example 3

[0088] The metal foil 10 with a carrier is prepared in the same manner as in Example 1, except that (i) a Ti layer is formed as the bonding layer 14a instead of the TaN layer, and (ii) a TaON layer is formed by reactive sputtering instead of performing surface oxidation treatment of the bonding layer 14a by atmospheric exposure.

[0089] (Formation of Ti Layer)

[0090] A Ti layer having a thickness of 100 nm was formed as the adhesion layer 14a by sputtering on the carrier 12. The sputtering was performed using the following apparatus and under the following conditions.

[0091] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0092] - Target: 8-inch (203.2 mm) diameter Ti target (99.999% purity)

[0093] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0094] -Gas: Argon (flow rate: 100 sccm)

[0095] -Sputtering pressure: 0.35Pa

[0096] -Sputtering power: 1000W (3.1W / cm 2 )

[0097] -Film forming temperature: 40℃

[0098] (Formation of TaON Layer)

[0099] A TaON layer having a target thickness of about 100 nm was formed on the surface of the adhesion layer 14 a by reactive sputtering using the following apparatus and conditions.

[0100] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0101] - Target: 8-inch (203.2 mm) diameter TaN target (99.98% purity)

[0102] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0103] -Gas: Argon (flow rate: 90 sccm) and Oxygen (flow rate: 10 sccm)

[0104] -Sputtering pressure: 0.35Pa

[0105] -Sputtering power: 100W (0.3W / cm 2 )

[0106] -Film forming temperature: 40℃

[0107] Example 4

[0108] The metal foil 10 with a carrier was produced in the same manner as in Example 2 except that a Ti layer with a thickness of 100 nm was formed as the adhesion layer 14 a instead of the TaN layer using the same apparatus and conditions as in Example 3.

[0109] Example 5

[0110] The metal foil 10 with a carrier was produced in the same manner as in Example 3 except that an Al layer was formed instead of the Ti layer as the adhesion layer 14a.

[0111] (Formation of Al Layer)

[0112] An Al layer having a thickness of 100 nm was formed as the adhesion layer 14a by sputtering on the support 12. The sputtering was performed using the following apparatus and under the following conditions.

[0113] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0114] -Target: 8-inch (203.2 mm) diameter Al target (purity 99.95% or more)

[0115] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0116] -Gas: Argon (flow rate: 100 sccm)

[0117] -Sputtering pressure: 0.35Pa

[0118] -Sputtering power: 1000W (3.1W / cm 2 )

[0119] -Film forming temperature: 40℃

[0120] Example 6

[0121] The metal foil 10 with a carrier was produced in the same manner as in Example 2 except that a 100 nm thick Al layer was formed as the adhesion layer 14a in place of the TaN layer using the same apparatus and conditions as in Example 5.

[0122] Example 7 (Compare)

[0123] The metal foil 10 with a carrier was produced in the same manner as in Example 1 except that only the Ta layer (adhesion layer 14a) was formed as the release functional layer 14 instead of the TaN layer (adhesion layer 14a) and the TaON layer (release layer 14b).

[0124] (Formation of Ta Layer)

[0125] A Ta layer having a thickness of 100 nm was formed as the adhesion layer 14a by sputtering on the carrier 12. The sputtering was performed using the following apparatus and under the following conditions.

[0126] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0127] -Target: 8-inch (203.2 mm) diameter Ta target (99.98% purity)

[0128] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0129] -Gas: Argon (flow rate: 100 sccm)

[0130] -Sputtering pressure: 0.35Pa

[0131] -Sputtering power: 1000W (3.1W / cm 2 )

[0132] -Film forming temperature: 40℃

[0133] Example 8 (Compare)

[0134] The metal foil 10 with a carrier was produced in the same manner as in Example 2 except that a Ta layer was formed instead of the TiON layer as the release layer 14 b.

[0135] (Formation of Ta Layer)

[0136] A Ta layer having a thickness of 100 nm was formed as the separation layer 14 b on the adhesion layer 14 a by reactive sputtering using the following apparatus and conditions.

[0137] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0138] -Target: 8-inch (203.2 mm) diameter Ta target (99.98% purity)

[0139] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0140] -Gas: Argon (flow rate: 100 sccm)

[0141] -Sputtering pressure: 0.35Pa

[0142] -Sputtering power: 100W (0.3W / cm 2 )

[0143] -Film forming temperature: 40℃

[0144] Example 9 (Compare)

[0145] The metal foil with a carrier 10 was produced in the same manner as in Example 1 except that the release layer 14 b was not formed (that is, the surface oxidation treatment of the adhesion layer 14 a was not performed).

[0146] Example 10 (Compare)

[0147] As the peeling layer 14b, Ta / TaO x The same operation as in Example 2 was performed to produce the metal foil 10 with a carrier except that the TiON layer was replaced by a Ta layer. Specifically, a Ta layer with a thickness of 100 nm was formed on the adhesion layer 14a using the same apparatus and conditions as in Example 8. The sample with the Ta layer formed was taken out of the vacuum and exposed to the atmosphere for 1 minute, thereby performing a surface oxidation treatment (natural oxidation) of the Ta layer. In this way, a Ta / TaO x The layer serves as the peeling layer 14b.

[0148] Example 11 (Compare)

[0149] like Figure 3 As shown, a release functional layer (adhesion layer 114, release auxiliary layer 116 and carbon layer 118 as a release layer), a second metal layer 120 and a first metal layer 122 are sequentially formed on a carrier 112 to produce a metal foil 110 with a carrier. The specific steps are as follows.

[0150] (1) Preparation of vector

[0151] A glass sheet (material: soda-lime glass, arithmetic mean roughness Ra: 0.6 nm) having a thickness of 1.1 mm was prepared.

[0152] (2) Formation of the adhesion layer

[0153] A Ti layer having a thickness of 100 nm was formed as the adhesion layer 114 on the carrier 112 by a sputtering method. The sputtering was performed using the following apparatus and under the following conditions.

[0154] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0155] - Target: 8-inch (203.2 mm) diameter Ti target (99.999% purity)

[0156] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0157] -Gas: Argon (flow rate: 100 sccm)

[0158] -Sputtering pressure: 0.35Pa

[0159] -Sputtering power: 1000W (3.1W / cm 2 )

[0160] -Film forming temperature: 40℃

[0161] (3) Formation of peeling auxiliary layer

[0162] A Cu layer having a thickness of 100 nm was formed as the peeling assisting layer 116 on the adhesion layer 114 by a sputtering method. The sputtering was performed using the following apparatus and under the following conditions.

[0163] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0164] - Target: 8 inch (203.2 mm) diameter copper target (99.98% purity)

[0165] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0166] -Gas: Argon (flow rate: 100 sccm)

[0167] -Sputtering pressure: 0.35Pa

[0168] -Sputtering power: 1000W (6.2W / cm 2 )

[0169] -Film forming temperature: 40℃

[0170] (4) Formation of carbon layer

[0171] An amorphous carbon layer having a thickness of 6 nm was formed on the peeling assisting layer by a sputtering method as the carbon layer 118. The sputtering was performed using the following apparatus and under the following conditions.

[0172] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0173] - Target: 8-inch (203.2 mm) diameter carbon target (99.999% purity)

[0174] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0175] -Gas: Argon (flow rate: 100 sccm)

[0176] -Sputtering pressure: 0.35Pa

[0177] -Sputtering power: 250W (0.7W / cm 2 )

[0178] -Film forming temperature: 40℃

[0179] (5) Formation of the Second Metal Layer

[0180] A Ti layer having a thickness of 100 nm was formed as the second metal layer 120 on the carbon layer by sputtering using the following apparatus and conditions.

[0181] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0182] - Target: 8-inch (203.2 mm) diameter Ti target (99.999% purity)

[0183] -Gas: Argon (flow rate: 100 sccm)

[0184] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0185] -Sputtering pressure: 0.35Pa

[0186] -Sputtering power: 1000W (3.1W / cm 2 )

[0187] (6) Formation of the First Metal Layer

[0188] A Cu layer having a thickness of 300 nm was formed on the second metal layer by sputtering as the first metal layer 122. The sputtering was performed using the following apparatus and under the following conditions.

[0189] · Equipment: Single-wafer magnetron sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)

[0190] - Target: 8-inch (203.2 mm) diameter Cu target (99.99% purity)

[0191] -Ultimate vacuum degree: less than 1×10 -4 Pa

[0192] -Gas: Argon (flow rate: 100 sccm)

[0193] -Sputtering pressure: 0.35Pa

[0194] -Sputtering power: 1000W (3.1W / cm 2 )

[0195] -Film forming temperature: 40℃

[0196] evaluate

[0197] The metal foils with carriers of Examples 1 to 11 were evaluated in various ways as shown below. The evaluation results are shown in Tables 1 and 2. Table 2 also shows the compositions of the adhesion layer (including the peeling auxiliary layer in Example 11) and the peeling layer as the peeling functional layer.

[0198] <Evaluation 1: Semi-quantitative analysis of peeling layer>

[0199] For Example 1, the depth direction analysis of the produced metal foil with carrier 10 was performed by X-ray photoelectron spectroscopy (XPS) according to the following measurement conditions and analysis conditions. The analysis was performed as follows: After the metal layer 16 was peeled off from the metal foil with carrier 10, the peeling function layer 14 was removed from the surface of the exposed layer toward the depth direction under the following conditions while being peeled off by Ar ion etching.

[0200] (Ar ion etching conditions)

[0201] -Accelerating voltage: 500V

[0202] - Etching area: 2mm×2mm

[0203] - Etching rate: 4.4nm / min in terms of SiO2

[0204] (Measurement conditions)

[0205] -Equipment: X-ray photoelectron spectrometer (Versa Probe III manufactured by ULVAC-PHI)

[0206] -Excitation X-ray: Monochromated Al-Kα ray (1486.6eV)

[0207] -Power: 50W

[0208] -Accelerating voltage: 15kV

[0209] -X-ray irradiation diameter: 200μmφ

[0210] -Measurement area: 200μmφ

[0211] - Pass energy: 26.0eV

[0212] -Energy step: 0.1eV

[0213] -Neutralizing gun: Yes

[0214] - Determination of elements and orbitals: (number of sweeps: rate: number of cycles)

[0215] C 1s: (3:6:1)

[0216] N 1s: (30:6:1)

[0217] O 1s: (5:6:1)

[0218] Cu 2p3: (2:6:1)

[0219] Ta 4d: (30:6:1)

[0220] (Analysis conditions)

[0221] XPS data were analyzed using data analysis software ("MULTIPAK Ver9.4.0.7" manufactured by ULVAC-PHI). Smoothing was performed at 15 points, and Shirley was used as the background mode. The background range of each element in the semi-quantitative calculation is as follows.

[0222] -C 1s: 280.0~292.0eV

[0223] -N 1s (including Ta 4p3): 392.0~410.0eV

[0224] -O 1s: 528.0~540.0eV

[0225] -Cu 2p3: 927.0~939.0eV

[0226] -Ta 4d: 212.0~250.0eV

[0227] Among them, the N 1s peak will interfere with the Ta 4p3 peak, so the semi-quantitative value of N 1s is calculated from the N1s peak area obtained by waveform separation analysis. The energy range of the peak position of N1s and Ta 4p3 in waveform separation analysis is shown below. In addition, the fitting function in waveform separation analysis uses a Gaussian function.

[0228] -N 1s: 395.9~398.2eV

[0229] -Ta 4p3 (metal): 399.5~400.5eV

[0230] -Ta 4p3 (oxide): 404.11~405.11eV

[0231] The results of the semi-quantitative values ​​in the depth direction of the metal foil 10 with a carrier of Example 1 are shown in Table 1. As is clear from Table 1, in the metal foil 10 with a carrier of Example 1, there is a region in which the atomic ratio of O constituting the TaON layer to the metal component (i.e., Ta) is 4% or more, and the atomic ratio of N constituting the metal nitride oxide to the metal component is 20% or more in the depth range from the surface of the peeling functional layer 14 (sputtering depth 0nm) to 2.9nm. Therefore, it is estimated that the thickness of the TaON layer (peeling layer 14b) in the metal foil 10 with a carrier of Example 1 is about 3nm in terms of SiO2.

[0232] [Table 1]

[0233] Table 1

[0234]

[0235] <Evaluation 2: Peelability of Carrier-Metal Layer>

[0236] The peel strength after vacuum hot pressing was measured as follows as a thermal history of the metal foil 10, 110 with a carrier. After the metal layer 16 side or the first metal layer 122 side of the metal foil 10, 110 with a carrier was subjected to flat plate electrolytic copper plating with a thickness of 18 μm, the thermal history was carried out at 260°C and 30 kgf / cm 2 The pressure was pressed for 2 hours. For the obtained copper-clad laminate, the peel strength (gf / cm) when the electroplated copper layer formed integrally with the metal layer 16 or the first metal layer 122 was peeled off was measured in accordance with JIS C 6481-1996. At this time, the measurement width was set to 50 mm and the measurement length was set to 20 mm. The peel strength (average value) obtained by the above operation was graded and evaluated according to the following criteria. The results are shown in Table 2.

[0237] - Evaluation A: Peel strength is 3 gf / cm or more and less than 30 gf / cm

[0238] -Evaluation B: Peel strength is 30 gf / cm or more and less than 50 gf / cm

[0239] - Evaluation C: The peel strength is less than 3 gf / cm or 50 gf / cm or more (including failure to peel), or peeling occurs between the carrier and the peeling functional layer and the evaluation cannot be performed.

[0240] <Evaluation 3: Number of foreign particles>

[0241] The number of foreign particles on the side surface of the metal layer 16 of the metal foil 10, 110 with a carrier or the side surface of the first metal layer 122 is measured as follows. First, a foreign matter inspection device (HS930 manufactured by Toray Engineering Co., Ltd.) is used to measure the total number of foreign particles (particle size is 5μm or more) on the surface of the metal foil with a carrier of a specified area. Then, the above total is divided by the measured area to calculate the number of foreign particles per unit area (1 square centimeter). It should be noted that the area from the end of the metal foil with a carrier to 10mm is set outside the measurement range. The number of foreign particles above 5μm per unit area obtained by this operation is graded and evaluated according to the following criteria. The results are shown in Table 2.

[0242] - Evaluation A: The number of foreign particles larger than 5 μm per 1 square centimeter is less than 0.20

[0243] - Evaluation B: The number of foreign particles of 5 μm or larger per 1 cm2 is 0.20 or more and less than 0.50

[0244] - Evaluation C: The number of foreign particles of 5 μm or larger per 1 square centimeter is 0.50 or more

[0245] <Overall Evaluation>

[0246] The comprehensive evaluation is determined based on the evaluation results of evaluation 2 and 3. That is, when the evaluation result of evaluation 2 is evaluation A or B and the evaluation result of evaluation 3 is evaluation A or B, it is judged as passed, and other cases are judged as failed. The results are shown in Table 2.

[0247] [Table 2]

[0248] Table 2

[0249]

[0250] * indicates a comparative example.

Claims

1. A metal foil with a carrier, comprising: Carrier; a release functional layer disposed on the support and comprising a metal oxynitride; and a metal layer disposed on the release functional layer, The peeling functional layer comprises: an adhesion layer provided on the carrier and comprising at least one selected from the group consisting of Cu, Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN; and The release layer is provided on the adhesion layer and contains at least one metal nitride oxide selected from the group consisting of TaON, NiON, TiON, NiWON and MoON.

2. The metal foil with a carrier according to claim 1, wherein The metal oxynitride includes at least one selected from the group consisting of TaON, NiON, TiON, NiWON, and MoON.

3. The metal foil with a carrier according to claim 1, wherein The adhesion layer contains 30 atomic % or more of at least one selected from the group consisting of Cu, Ti, Ta, Cr, Ni, Al, Mo, Zn, W, TiN and TaN.

4. The metal foil with a carrier according to claim 1, wherein The thickness T1 of the adhesion layer is greater than or equal to 5 nm and less than or equal to 400 nm.

5. The metal foil with a carrier according to claim 1, wherein In the release layer, the atomic ratio of O constituting the metal oxynitride to the metal component measured by X-ray photoelectron spectroscopy (XPS) is 4% or more, and the atomic ratio of N constituting the metal oxynitride to the metal component is 20% or more.

6. The metal foil with a carrier according to claim 1, wherein The thickness T2 of the peeling layer is greater than or equal to 1 nm and less than or equal to 150 nm.

7. The metal foil with a carrier according to claim 1, wherein The ratio of the thickness T1 of the adhesion layer to the thickness T2 of the release layer, ie, T1 / T2, is 0.03 or more and 400 or less.

8. The metal foil with a carrier according to claim 1 or 2, wherein The carrier is made of glass, silicon or ceramic.

9. The metal foil with a carrier according to claim 1 or 2, wherein: The metal layer is composed of at least one metal or alloy selected from the group consisting of Cu, Au, and Pt.

10. The metal foil with a carrier according to claim 1 or 2, wherein The thickness T3 of the metal layer is greater than or equal to 10 nm and less than or equal to 1000 nm.

Citation Information

Patent Citations

  • Substrate for supporting circuit formation, and substrate for packaging semiconductor element and its manufacturing method

    JP2005101137A

  • Copper foil with carrier, manufacturing method of copper foil with carrier, laminate, manufacturing method of printed wiring board and manufacturing method of electronic device

    JP2017088970A

  • Copper foil with carrier

    WO2019131000A1

  • Conductive laminate for touch panel

    JP2017220150A